1995
DOI: 10.1097/00000539-199504000-00018
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacokinetics and Neuromuscular Effects of Rocuronium Bromide in Patients with Liver Disease

Abstract: To determine the effect of liver disease on the pharmacokinetics of rocuronium, the authors administered 0.6 mg/kg (twice the ED95) to 10 patients with liver disease and compared these results to values in 10 healthy surgical patients. Anesthesia was induced with thiopental and maintained with isoflurane (0.9%-1.1% end-tidal concentration) and nitrous oxide (60%). Venous blood samples were obtained for 6 h after rocuronium injection and plasma concentrations were measured using gas chromatography. Pharmacokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
3

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 18 publications
1
26
0
3
Order By: Relevance
“…Remifentanil was not used in any of these cases. Elimination of vecuronium and rocuronium in cases of hepatic cirrhosis and other severe liver dysfunction is reduced, especially in patients with repeated injections and a long infusion time [38,39,40,41]. Although plasma cholinesterase levels are reduced in pregnancy and hepatic disease and there have been reports of prolonged neuromuscular blockade after a second dose in cases of AFLP, succinylcholine is still recommended as the muscle relaxant for rapid-sequence induction [42].…”
Section: Discussionmentioning
confidence: 99%
“…Remifentanil was not used in any of these cases. Elimination of vecuronium and rocuronium in cases of hepatic cirrhosis and other severe liver dysfunction is reduced, especially in patients with repeated injections and a long infusion time [38,39,40,41]. Although plasma cholinesterase levels are reduced in pregnancy and hepatic disease and there have been reports of prolonged neuromuscular blockade after a second dose in cases of AFLP, succinylcholine is still recommended as the muscle relaxant for rapid-sequence induction [42].…”
Section: Discussionmentioning
confidence: 99%
“…The latter finding may depend on an increased V dss of ropivacaine. The V dss of other drugs, such as rocuronium 79 and propofol, 80 is also increased in patients with hepatic dysfunction. When repeated doses 25 or continuous infusions are used, the accumulation of both bupivacaine and ropivacaine and of their metabolites needs to be considered, and doses should be reduced accordingly.…”
Section: Patient-related Factors To Be Considered When Large Doses Ofmentioning
confidence: 99%
“…The authors concluded that, as the drug is thought to be eliminated mainly by biliary excretion, biliary excretion of the drug is perhaps preserved in cirrhosis. [73] Nevertheless, a study of long term bismuth administration to cirrhotic rats found substantial plasma and tissue accumulation of bismuth over a 70-day period, due to reduced biliary and renal eliminationP4] The authors concluded that patients with cirrhosis may therefore be at risk of a similar accumulation of bismuth and of other metals sharing common mechanisms of disposition.…”
Section: Biliary Excretionmentioning
confidence: 99%